Laser Induced Breakdown Spectroscopy: A Promising Analytical Technique - Mehta, Preeti; Populwar, Vaishnavi; Shinde, Nilima; Dhebe, Dattatray; More, Pratik (Indian Journal of Pharmaceutical Education and Research, 2025)
Laser Induced Breakdown Spectroscopy (LIBS) is a rapid analytical technique. It has become an established analytical atomic spectrometry technique for the analysis of various samples. This method is widely used for determination of the elemental composition of various solids, liquids and gases as well as for the characterization and identification of the material. This technique is based on the optical detection of certain molecular and atomic species. Present review article aims to provide all the basic information related to Laser induced breakdown spectroscopy. In this review article, all the aspects of LIBS such as history, principle, instrumentation, advantages, limitations, as well as applications are described in brief.
Keywords: Laser Induced Breakdown Spectroscopy; Calibration Free Laser Induced Breakdown Spectroscopy; Analytical technique; Laser Induced Plasma Spectroscopy; Laser Spark Spectroscopy